Purple cabbage (Brassica oleracea L.) cookies as nutraceutical product for Maintaining Healthy Heart - Salsabila Eka Setia Ningrum; Ludy Wiji Lestari; Reza Maulinda Nur Cahya Berlianti; Asyifaul Khasanah; Faza Saiqur Rahmah; Mayu Rahmayanti (Indonesian Nutrition Association, 2023)
Purple cabbage (Brassica oleracea L.) is one of the agricultural products that contain anthocyanins which have the potential as antioxidants. The amount of production in Indonesia is still relatively low due to a lack of consumer demand and a lack of innovation in its utilization. So it is necessary to make new innovations, one of which is by processing it into flour to make Almond Crispy which is then given the name